Stylasteridae (Cnidaria, Hydrozoa, Filifera) from South Africa - Cairns, Stephen D.; Zibrowius, Helmut (Zootaxa, 2013)
We describe and figure the 20 species of stylasterid hydrozoans known from South Africa. These consist of seven new species, six range extensions, and seven species previously known from South African. Most of the specimens reported resulted from expeditions of the Pieter Faure (1898–1903) and Meiring Naudé (1975–1987), and are deposited primarily in the South African Museum (Cape Town). A replacement name (Errina australis) is proposed for the junior homonym Errina hicksoni Cairns, 1991. A brief history of species discovery of the South African stylasterids is presented. The new morphological term dactyloglossa is introduced to define a baffle-like structure found in dactylopores of some species. Of the 20 South African species, 12 (60%) are not yet known outside that area. Three patterns of distribution were noted: species confined to the tropical region of South Africa, those found in both the tropical and warm temperate regions of S. Africa, and those found only in the warm temperate regions, three in the latter group sharing their distribution with cold temperate southern South America and two with warm temperate New Zealand, representing a circum-southern temperate distribution.